Exploring collocation development in L2 German from students’ perspective: A contrasting case study - Boone, Griet; Eyckmans, June (Studies in Second Language Learning and Teaching, 2023)
Despite the growing body of studies on collocation learning in SLA research, there are hardly any studies taking the perspective of the individual learner or studies that have examined the effect of individual differences. This study–a qualitative component of a mixed-methods longitudinal project–presents an in-depth exploration of the intro- and retrospective views of five Dutch-speaking L2 students of German on their 3-year collocation learning process. It focuses on the individual factors that enhanced or hindered L2 collocation development, and on the extent to which effective and less effective collocation learners differed regarding their L2 motivation, exposure and use, learning experience, and learning strategies. Extreme sampling strategy was used and five contrasting cases of learners were selected (three effective versus two less effective collocation learners). Data were gathered through semi-structured interviews and learners’ written reflections on five specific collocations. Findings indicate that the effective collocation learners showed a higher intrinsic motivation, more engagement in informal learning activities, more extensive social interaction in the L2, more awareness towards collocations, a higher degree of self-regulation, and a higher number of learning strategies than the less effective collocation learners. Based on these findings, pedagogical implications are provided.